Bibliometric analysis of global research trends between gut microbiota and pancreatic cancer: from 2004 to 2023 - Wu, Shuang; Wen, Su; An, Kangli; Xiong, Liping; Zeng, Hao; Niu, Yueyue; Yin, Tiejun (Frontiers in Microbiology, 2023)
Abstract Background: Pancreatic cancer (PC) is one of the most lethal malignancies of the digestive system and is expected to be the second leading cause of cancer-related death in the United States by 2030. A growing body of evidence suggests that the gut microbiota (GM) is intimately involved in the clinical diagnosis, oncogenic mechanism and treatment of PC. However, no bibliometric analysis of PC and GM has been reported. Methods: The literature on PC and GM was retrieved from the Web of Science Core Collection (WoSCC) database for the period from January 1, 2004 to April 25, 2023. Microsoft Excel 2021, CiteSpace, VOSviewer, Scimago Graphica, Graphpad Prism, Origin, the R package “bibliometrics” and the bibliometric online analysis program were used to visualize the publishing trends and hot spots in this field. Results: A total of 1449 articles were included, including 918 articles and 531 reviews. Publishing had grown rapidly since 2017, with the 2023 expected to publish 268 articles. Unsurprisingly, the United States ranked highest in terms of number of literatures, H index and average citations. The University of California System was the most active institution, but Harvard University tended to be cited the most on average. The three most influential researchers were Robert M Hoffman, Zhao Minglei and Zhang Yong. Cancers had published the most papers, while Nature was the most cited journal. Keyword analysis and theme analysis indicated that “tumor microenvironment”, “gemcitabine-resistance”, “ductal adenocarcinoma”, “gut microbiota” and “diagnosis” will be the hotspots and frontiers of research in the future. Conclusion: In summary, the field is receiving increasing attention. We found that future hotspots of PC/GM research may focus on the mechanism of oncogenesis, flora combination therapy and the exploitation of new predictive biomarkers, which provides effective suggestions and new insights for scholars.